Coping with coastal risk and vulnerabilities in Bangladesh. (June 2015) - Fakhruddin, S.H.M.; Rahman, Juma
Abstract: Livelihoods in the coastal zone are vulnerable to a variety of shocks (e.g. cyclone), trends (e.g. climate change) and seasonality (e.g. salinity). This is probably due to economic and social susceptibility. In a developing economy, vulnerability is also studied in terms of the power aspects of gender (the inequality in power relations between men and women), and manifested in the marginalization of (mostly) women in social, economic, political and cultural spheres of life. However, gender related vulnerability to disasters is a socially created form of vulnerability. This paper focuses on understanding gender-differentiated impacts on different livelihoods and how they affect the formulation of policies, programs or projects. It also examines how this input into program formulation reduces the level of risk faced by poor people and enhances their resilience and ability to cope with stresses. The results show that some coping mechanisms are directly enacted at the individual or household level (limits on food consumption, sale of assets, and so forth) and some are enacted at the livelihood group level, where people devise their coping strategies on a more occupational and livelihood-based domain. People enact these strategies in a group manner and react according to their basic needs and the requirements of their livelihoods.